PERTUSSIS INCIDENCE AND THE EFFECT OF REVACCINATION OF PRESCHOOL AND SCHOOL CHILDREN - А. M. Kostinov (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The review is devoted to the analysis of pertussis incidence of children in the age group of 5–7, as well as strategies of DTP immunization with the help of the drugs in foreign countries. Mass vaccination against pertussis began in the middle of the 20th century, which contributed to a reduction in incidence and mortality rate from this infection. However, in the last decade, there has been an opposite tendency of increasing incidence of patients among children under school age, school age and adults. Atypical forms of the disease and complications due to ARVI, respiratory mycoplasmosis and cytomegalovirus infections are described in the review. Various strategies for the use of whole-cell and acellular pertussis vaccines as part of DTP drugs are described, as well as the epidemiological effect of introducing an additional booster dose of vaccine to children under school age. The expediency of revaccination of children aged 6–7 in Russia is argued, which can help to reduce the overall incidence of pertussis. The research materials related to the study of the properties of acellular anti-pertussis vaccine, such as immunogenicity and safety in comparison with whole-cell vaccine, are analyzed. The main drugs and their composition, which are used to vaccinate children against pertussis, are described in the review. It is assumed, that the increase in the incidence among children and teenagers, with the appearance of atypical forms of pertussis, is associated with a number of factors, such as the spread of new genotypes of Bordetella pertussis bacterium, emerged from mutations, as well as short duration of immunity after vaccination with acellular drugs, in comparison with whole-cell, and the use of more modern methods of detecting the pathogen. The mechanisms of the immune response due to different types of pertussis vaccines are also reviewed. It is concluded, that revaccination of children aged 6–7 with an additional fifth dose of an acellular vaccine against pertussis, as part of the DTaP instead of the Td drug, which is regulated in the National Calendar of preventive vaccinations, will have a favorable effect on the epidemic situation with pertussis infection in Russia.